A Production and Operations Management Study on Exal Industries Corporation - Balois, Stephanie; Casal, Michelle Mare.; Caw, Eunice; Tongco, Serafin Benedicto II. (Diliman, Quezon City College of Engineering, 2003)
Exal Industries Corporation specializes in making toothpaste and industrial tubes. They have their won line of toothpaste which is Meisu Plus. They also subcontract for other companies, the top two of which are TVP Dental and Multi-Rated Manufacturing. The study aimed to help the company reduce production costs by focusing on three core problems. The first problem in the study is that the company uses the wrong forecasting approach. Because of this, they are not able to properly estimate the number of units to produce. Based on Pareto analysis, three brands anf their products were studied. These are Meisu Plus ( 50 ml, 100 ml, and 150 ml), TVP Dental (10 ml) and Multi-Rated Manufacturing (25 ml, 50 ml, 100 ml and 150 ml). The different techniques were then evaluated using Mean Average Deviation and Tracking Signal. THe results showed that Trend-Adjusted Exponential Smoothing is appropriate fir Meisu Plus 50 ml (a=0.6, b=0.2) Multi Rated 25 ml (a=0.6, b=0.3), Multi-Rated 25 ml (a=0.6, b=0.3), Multi-RAted 50 ml (a=0.4, b=0.1), Multi-Rated 100 ml (a=0.4, b=0.1) and Multi-Rated 150 ml (a=0.6, b=0.3) while Exponential Smoothing is most appropriate for TVP Dental (a=0.1). No test passed for Meisu Plus 100 ml and 150 ml. Because of this, the group recommends that the company continue to use their current forecasting method for the meantime. The second problem deals with capacity analysis. The press machine was originally designed for only one size and the company adjusted it to make it suitable for other sizes. This results in a lot of downtime and changeover time, making the press have a low output rate of 1843.063 pieces per hour. This makes it the bottleneck of the process. The company is currently considering to purchase a second hand press costing P500,000. Using NPV analysis, it was determined that it is more beneficial for the company to purchase the second hand press. By doing so, the company will be able to save 1,695 hours of overtime which translated to an annual savings of P66,243.75. Lastly, the third problem is that the company does not have an inventory system, Due to the nature of the company's operations, the basic Economic Order Quantity Model was used. The four most used raw materials were analyzed. These are zinc stearate, lacquer, coating and slugs. The reorder points and reorder quantities were determined. The order quantities for zinc stearate, lacquer and coating are 3.41 kg, 17.53 L, and 3.09 L, respectively. The order quantities for the different slug sizes are 1.1 kg for 10 ml, 1.43 kg for industrial sizes, 2.68 kg for 100 ml and 1.41 kg for 50 ml. The reorder points are 0.5818 kg for 10 ml, 0.9746 kg for industrial sizes, 3.3070 kg for 100 ml and 0.9155 kg for 50 ml. To aid the company in their inventory record-keeping, the group also suggested a format for the forms the company can use. It is suggested that the company check their inventory weekly so that they can easily detect whether they need to reorder or not. No additional cost occurs in this new policy because the company already has a stockman to do the job. He just has to be taught the proper method of implementing the inventory check.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Exal Industries Corporation; Manufacturing industries; Production engineering